"At the hospital they do not treat venom from snakebites": A qualitative assessment of health seeking perspectives and experiences among snakebite victims in Rwanda. (June 2022) - Schurer, Janna M.; Dam, Aleta; Mutuyimana, Marie Thérèse; Runanira, Daniel Muhire; Nduwayezu, Richard; Amuguni, J. Hellen
Abstract: Snakebite envenomation (SBE) is a serious medical condition with human, animal, and environmental factors driving occurrence. In Rwanda, the number of SBE cases reported by the medical system is far lower than regional estimates for SBE incidence, suggesting that victims might be seeking care outside of formal medical structures. Our goals were to describe circumstances surrounding snakebite and to explore experiences of snakebite victims in accessing treatment. For this qualitative study, our team recruited individuals bitten by snakes between 2013 and 2018, who sought care either from traditional healers (N = 40) or hospitals (N = 65). In-depth interviews based on a semi-structured interview guide were conducted by telephone in Kinyarwanda. Inductive thematic analysis was conducted by two team members. Our respondents reported similar environmental circumstances surrounding their snake encounters; namely, farm fields, roads, and their homes, as well as inadequate lighting. Unsafe First Aid practices, including burning/sucking/cutting the skin and tourniquet, were often performed immediately after bites. Respondents reported various reasons for seeking traditional or hospital care, such as perceived cost, distance, transportation, and especially, community beliefs and treatment outcomes of other victims. Respondents described envenomation of livestock as well as the sale of livestock to pay SBE-related medical expenses. Improving trust and use of formal medical services will require enhanced hospital delivery of high quality medical services for SBE through improved stocking of appropriate anti-venom and reduced delays during intake. Communities might also benefit from education campaigns that discourage unsafe First Aid practices and address the common misperception that physicians are not trained to treat SBE. Graphical abstract: Image 1 Highlights: Snakebite victims engage in unsafe First Aid practices such as burning, cutting, sucking the wound. Treatment outcomes of other victims influenced decisions to seek traditional medicine or hospital care. Livestock bitten by snakes were treated by veterinarians or traditional healers, or received no care.